Social Impact of a Transformative Service-Learning Experience in a Post-conflict Setting - Trigos-Carrillo, Lina; Fonseca, Laura; Reinoso, Natalia (Frontiers in Psychology, 2020)
In the context of the 2016 Peace Agreement signed between the Colombian government and the FARC-EP (Fuerzas Armadas Revolucionarias de Colombia-Ejército del Pueblo), several challenges for society and academia have emerged: (1) Overcoming the gap between the rural and urban settings, which has been one of the roots of the Colombian armed conflict, and (2) training psychologists and transforming traditional educational practices, which have not been designed to fulfill community needs in a post-conflict setting. One of the strategies from academia to overcome these difficulties is to create alliances with rural communities where students learn key competences to foster a horizontal approach while actively working with the community. In the region of Caquetá, Colombia, two Territorial Spaces for Training and Reincorporation (ETCR) were created in order to provide a space for former guerrilla members’ reincorporation to civil society. In the ETCR Héctor Ramírez, twenty-seven students and two faculty participated in a service-learning project (two weeks in December 2018 and two in June 2019) where they engaged in local daily practices and social projects based on the community’s prioritized needs. The aim of this study was to analyze the learning process of undergraduate psychology students in this community psychology service-learning project in the context of peacebuilding in Colombia. This study is grounded in a Participatory Action Research (PAR) approach. Data collected includes reflective narratives and video diaries by students before and during the course, and two focus groups after the experience. Findings suggest that students who participated in the experience are in the process of developing cultural humility, through affective understandings and the consolidation of communities of practice that include the former guerrilla members and their knowledges. Preparing psychologists to lead peace building and reconciliation processes is of importance to the field because the professional competencies gained in this context surpass the professional practice as they become part of the students’ abilities as citizens. The social impact is twofold: the students learn to create partnerships where purposes are co-constructed and trust-based, while the community takes the lead of their processes creating alliances with an academia that recognizes their knowledge and practices.